Examining female identity in selected writings of Nathaniel Hawthorne - Suhadi, Agung (2014)
This study investigates the effect of the prevailing patriarchal oppression towards female characters in Nathaniel Hawthorne's short stories searching for identity through the lens of radical feminism, focusing specifically on authority and power. It can be seen that Hawthorne demonstrates how female characters struggle to defme their lives as best as they can under male societal strictures in the early 19th century. The rationale is that by understanding the effect of dominant patriarchal culture in the selected writings, the motivation towards the quest of identity among women of the period can be better understood. Hence, Hawthorne's collection of short stories serves as an indication and polemic of what happens to women when they are not allowed to attain their own identity independently of the men. This thesis analyses the selected writings of Nathaniel Hawthorne namely Minister's Black Veil (1836), Wakefield (1843), Birthmark (1843), Rappacini's Daughter (1844) and Scarlet Letter (1850). The result of this study reveals that Hawthorne has challenged patriarchal oppression through his writings, but he explores in different ways such as "confrontation", "bravery", "death as a triumph" and "self-reliance". In short, this research shows that Hawthorne in some ways exalts the rights of women to seek their own identity in society.